Stereoselective synthesis and molecular modeling of chiral cyclopentanes. (13th October 2015) - Abdel-Jalil, Raid J.; Steinbrecher, Thomas; Al-Harthy, Thuraya; Mahal, Ahmed; Abou-Zied, Osama K.; Voelter, Wolfgang
Highlights: We developed an easy access to asymmetric synthesis of cyclopentane. Simulations indicate the dominant role of the β-L sugar intermediate in the reaction. We show the difference in the preferred conformation leading to the target product. Graphical abstract: Abstract: The reaction of 3-methyseleno-2-methylselenomethyl-propene with benzyl 2, 3-anhydro-4- O -triflyl-β-L-ribopyranoside provides a major convenient enantiomeric product of 1-methylene-(benzyl3, 4-dideoxy-α-D-arabinopyranoso)-[3, 4-c]-cyclopentane, with benzyl-2, 3-anhydro-4-deoxy-4- C -(2-methyl- propen-3-yl)-α-D-lyxopyranoside as a minor product. While the reaction of 3-methyseleno-2-[methylselenomethyl]-propene with benzyl 2, 3-anhydro-4- O -triflyl-α-D-ribopyranoside produces a good yield of benzyl-2, 3-anhydro-4-deoxy-4- C -(2-methylpropen-3-yl)-α-D-lyxo-pyranoside. Molecular modeling and molecular dynamics simulations indicate that the intermediate in the reaction of the β-L sugar frequently occupies an optimal conformation that leads to the formation of cyclopentane, while the intermediate in the reaction of the α-D sugar has a very small probability. The results point to the dominant role of the β-L sugar intermediate in controlling the cyclopentane formation.